Imaging mass spectrometry for accessing molecular changes during burn wound healing. Issue 5 (26th July 2016) - Taverna, Domenico; Pollins, Alonda C.; Sindona, Giovanni; Caprioli, Richard M.; Nanney, Lillian B.
ABSTRACT: The spatiotemporal analysis of the proteomic profile during human wound healing is a critical investigative step that can establish the complex interplay of molecular events that comprise the local response to burn injury. Partial‐thickness wound samples with adjacent "normal" skin were collected from twenty‐one patients with burn wounds and examined across a time spectrum ranging from the acute injury period at 3, 6, 11 days to the later hypertrophic scar period at 7 and 15 months. The techniques used for histology‐directed tissue analyses highlighted inflammatory protein markers at the early time points after injury with diminished expression as burn wounds progressed into the proliferative phase. The datasets show the usefulness of MALDI MS and imaging mass spectrometry as discovery approaches to identify and map the cutaneous molecular sequence that is activated in response to the unique systemic inflammatory response following burn trauma. This information has the potential to define the unique factors that predispose human burn victims to disfiguring hypertrophic scar formation.